Synergistic Action of 17-B Estradiol and Bisphenol A in Pituitary Cell Lines. - Korb, Sarah (My University, 2009)
The gonadal steroid 17 B-estradiol (E2) is produced primarily by the ovaries and regulates gene regulation, growth and differentiation in a number of target tissues, including the pituitary gland, where E2 regulates the production and/or release of hormones such as prolactin and luteinizing hormone. These studies examine changes in gene transcription following coadministration of E2 and a variety of E2 mimics.
Synergistic Action of 17-beta Estradil and Bisphenol A in Pituitary Cell Lines
Color poster with text, images, and graphs describing research conducted by Sarah Korb, advised by Winnifred M. Bryant.
Keywords: Pituitary gland; Estradiol--Physiological effect; Bisphenol A--Physiological effect; Sterols--Physiological effect; Gene expression; Phenols--Physiological effect; Posters